Syntactic and discursive maturity of students of 3rd of ESO - Esteruelas, Pedroviejo Juan Manuel (Romanica Olomucensia, 2022)
To assess syntactic and discursive maturity, it is necessary to measure the ability to produce complex syntactic units and to cohere a text through discourse connectors and sequences of direct and indirect speech that respect deictic references. In this study, the degree of syntactic and discursive complexity of a narrative text written by adolescents studying their 3rd year of ESO is verified. To do this, the variables of the sex and academic level of the students are taken into account, on the one hand, and, on the other hand, the syntactic maturity evaluation indices used since Kellogg Hunt (1970), which are basically the minimum unit terminals (t-units) and the clauses and the discursive maturity evaluation indices that allow the checking of the cohesion of the discursive elements in relation to the topic that give coherence to the text. The methodology used is the quantitative analysis of the proposed evaluation indices, which provides objectivity and exhaustiveness, and a comment based on the results, considering that the higher the academic level of the student, the greater the complexity of the text prepared and, consequently, the greater its syntactic and discursive maturity. This research, in fact, aspires to verify the importance of the academic level of the students in the development of the acquired syntactic and discursive maturity and, on the contrary, the irrelevance that the sex of the students has in this same process.
Keywords: syntactic maturity; discursive maturity; syntactic complexity; units of analysis